Up-regulation of microRNA miR-101-3p enhances sensitivity to cisplatin via regulation of small interfering RNA (siRNA) Anti-human AGT4D and autophagy in non-small-cell lung carcinoma (NSCLC). Issue 1 (1st January 2021) - Cui, Dong; Feng, Yu; Qian, Rulin
ABSTRACT: The emergence of drug resistance hinders the treatment of malignant tumors, and autophagy plays an important role in tumor chemotherapy resistance. However, its mechanism in non-small cell lung cancer (NSCLC) has not been well-researched. We aim to investigate the role of miR-101-3p in cisplatin-resistant via regulation of autophagy-related protein 4D (ATG4D) and autophagy. Cell viability, apoptosis, fluorescence intensity of GFP-LC3 and RFP-GFP-LC3 were determined using Cell Counting Kit-8 (CCK-8) assay, flow cytometry, and Laser scanning confocal microscope analysis, respectively. The levels of LC3II/LC3I, P62 and ATG4D were detected by Western blot. The results showed that the sensitivity to cisplatin in NSCLC cells was up-regulated by miR-101-3p mimics treatment, inducing promoting cell apoptosis and inhibiting autophagy. Further mechanistic study identified that ATG4D was a direct target of miR-101-3p. Moreover, ATG4D siRNA also could reverse miR-101-3p inhibitor-induced the up-regulation of ATG4D and the ration of LC3II/LC3I, the down-regulation of p62 expression. Our findings indicated that miR-101-3p could regulate sensitivity to cisplatin of NSNCC cells by regulating autophagy mediated by ATG4D. Therefore, miR-101-3p may act as a potential therapeutic target for the treatment of NSCLC.